Online Information and Mentorship: Perspectives From Orthopaedic Surgery Residency Applicants. Issue 14 (15th July 2021) - Yong, Taylor M.; Austin, Daniel C.; Molloy, Ilda B.; Torchia, Michael T.; Coe, Marcus P.
Abstract : Introduction: Applying to orthopaedic surgery residency is competitive. Online information and mentorship are important tools applicants use to learn about programs and navigate the process. We aimed to identify which resources applicants use and their perspectives on those resources. Methods: We surveyed all applicants at a single residency program for the 2018 to 2019 application cycle (n = 610) regarding the importance of online resources and mentors during the application process. We defined mentorship as advice from faculty advisors or counselors, orthopaedic residents, medical school alumni, or other medical students. We also assessed their attitudes about the quality and availability of these resources. Applicants were asked to rank resources and complete Likert scales (1 to 5) to indicate the relative utility and quality of options. Descriptive statistics were used to summarize data for comparisons. Results: The response rate was 42% (259 of 610 applicants). Almost 50% of applicants reported that they would have likely applied to fewer programs if they had better information. Applicants used program websites with the highest cumulative frequency (96%), followed by advice from medical school faculty/counselors and advice from orthopaedic residents at home institution (both 82%). The next two most popular online resources were a circulating Google Document (78%) and the Doximity Residency Navigator (73%). On average, the quality of online resources was felt to be poorer than mentorship with advice from orthopaedic residents receiving the highest quality rating (4.16) and being ranked most frequently as a top three resource (122 votes). Mentorship comprised three of the top five highest mean quality ratings and three of the top five cumulative rankings by usefulness. Conclusion: Applicants reference online resources frequently, despite valuing mentorship more. If the orthopaedic community fostered better mentorship for applicants, they may not feel compelled to rely on subpar online information. Both online information and mentorship can be improved to create a more effective application experience.